Koperasi Sebagai Wahana Pembelajaran, Serta Pembentukan Perilaku Berkoperasi: Studi Kasus Pada Koperasi Mahasiswa Kota Bandung - Yuanita Indriani (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
University Students, are millennials, which makes up almost 60 percent of the total population of Indonesia, do not understand and are not interested in cooperatives, even though the founders of the nation emphasized that the most suitable economic structure for the Indonesian people is cooperatives. There are indications that students' interest in cooperating through Student Cooperatives is still minimal. Some of the questions that arise are: why Student Cooperatives are not attractive to students, whether Student Cooperatives is a good place to learn cooperative values, and whether students who have joined the cooperative have a preference for developing cooperatives in the future. This study uses quantitative methods, the locus of research is the city of Bandung, the number of Kopma samples is 5, determined purposively. Research respondents were students (as members, administrators and supervisors as well as managers). The results showed that Kopma had provided cooperative experiences for its members, and the experiences gained were in the form of negative experiences and positive experiences; Students who get positive experiences from Student Cooperatives have a high tendency to replicate cooperative activities in the community.